KONSTRUKSI MOTIF DALAM PEMBUKTIAN PERKARA PIDANA - Adrianus Herman Henok (Honeste Vivere, 2023)
Hans Jonas in the Ethics of Responsibility states that "Every time you take an action, also imagine the consequences of that action, meaning that if the action is bad then also imagine the bad consequences that will occur, conversely if the action is good then also imagine the good consequences that will occur, or in other words every action has good consequences such as rewards, as well as bad consequences, such as punishment." The purpose of this study is to examine the construction of motives in proving a criminal case based on positive law in Indonesia. The method used is normative juridical with analytical descriptive analysis by searching secondary data through various relevant legal materials. From the research it was concluded that motive plays an important role in proving the elements of a crime in a criminal case, especially those associated with elements of error and in the future motives will be increasingly relevant in relation to the goals and guidelines of sentencing.